Estresse oxidativo, inflamação e apoptose em modelo in vitro da doença hepática gordurosa associada ao metabolismo - Arruda, Vinícius Marques (2023)
Metabolism-associated fatty liver disease (MAFLD) represents a broad clinical-pathological spectrum involving steatosis and steatohepatitis with possible progression to cirrhosis and hepatocellular carcinoma. With the lipid overaccumulation within hepatocytes, characteristic of steatosis, the progression of MAFLD is due to the joint action of several factors, especially oxidative stress, which drives to inflammation and apoptosis. This multisystem disorder is the most common chronic liver disease, and although it affects around a quarter of the global population, it still has no established treatment. The present study aimed to evaluate markers of oxidative stress, inflammation and apoptosis by the establishment of an in vitro model of MAFLD. Lipid accumulation was induced in HepG2 cells by exposure to oleic and palmitic acids at different concentrations for 24 and 48 hours and evaluated qualitatively and spectrophotometrically after staining with Oil Red O. Viability and cell damage were determined by the MTT method and by the activity of the enzymes lactate dehydrogenase and aminotransferases released in the culture media. Oxidative stress was assessed by quantifying biomarkers of lipid peroxidation, protein carbonylation, and total and reduced glutathione levels. Protein expression of inflammation and apoptosis intermediates was also analyzed using the western blotting technique. The results reveal the effectiveness of the model in promoting steatosis and oxidative stress in HepG2 cells, especially when exposed to a mixture of oleate and palmitate at 2 mM, showing increased levels of biomarkers of redox state. In agreement with these results, the ratios of oxidized and reduced levels of glutathione suggest significant changes in the glutathione system in response to increased lipid peroxidation, which may be related to increased expression of NF-κB, indicating possible activation of the inflammatory process. On the other hand, more expressive reductions in cell viability associated with a cytotoxic effect were found in cells exposed to palmitic acid, consistent with a greater expression of caspase-3, which reinforces the lipotoxic effect of saturated fatty acids. Therefore, the proposed model constitutes a useful and relevant tool for the investigation of molecular mechanisms and therapeutic approaches for MAFLD.